Pengembangan Modifikasi Permainan Monopoli sebagai Media Pembelajaran pada Materi Peluang Kelas VIII SMPN 1 Narmada Tahun Ajaran 2022/2023 - Aprilia Listiana; Muhammad Turmuzi; Eka Kurniawan; Sudi Prayitno (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to develop a monopoly game as a learning medium in class VIII opportunity material at SMPN 1 Narmada that is valid and practical. The type of research used is development research by adopting five steps in the ADDIE stage, namely analysis, design, development, implementation, and evaluation. The sample in this study was class VIII.3, which consisted of 30 students. The data collection technique was a questionnaire to measure the validity of the media which was distributed to 5 validators namely 2 mathematics lecturers at the University of Mataram and 3 mathematics teachers at SMPN 1 Narmada and student response questionnaires which were used to measure the practicality of the media which were distributed to class VIII.3. The results showed that the calculation of the learning media validation questionnaire was declared valid based on the Aiken index category with a value of V = 0.898 and the student response questionnaire results obtained were Practical based on the practicality category with a percentage value of 76%. Based on the results of these calculations, it is stated that this learning media can already be used for learning in schools, especially in the subject of opportunities.